An unusual cause of ST elevation myocardial infarction (STEMI). (22nd September 2014) - Monem, Mohammed; Rampat, Rajiv
Abstract : A 67-year-old Caucasian woman presented to clinic with a 2-month history of worsening shortness of breath on exertion and a single episode of chest pain 1 week before. Her ECG in clinic showed ST elevation inferiorly and she was admitted from clinic for further investigations as inpatient. She was initiated on the acute coronary syndrome protocol and underwent emergency left heart catheterisation on the day of admission. The coronary angiogram revealed large aneurysmal dilations in the right coronary artery and left main stem. A ventriculogram showed poor left ventricular (LV) systolic function in line with subsequent transthoracic echocardiogram, which revealed her to have an left ventricular ejection-fraction (LVEF) of approximately 20%. It was agreed with the cardiothoracic surgeons to treat the aneurysms non-operatively and start low-molecular weight heparin. Furthermore the underlying biventricular impairment was treated with ACE-inhibitors, β-blockers and diuretic therapy (loop and potassium-sparing). The strategy was to prevent further thrombus formation with the aneurysmal vessels and to achieve this the patient was initiated on lifelong warfarin. Other medical risk factors were optimised and patient started on statin medication. The aneurysm was monitored with serial CTs with a view to reconsider surgical intervention if any evidence of dilation. This case highlights an unusual cause of ST elevation myocardial infarction.